The tissue distribution and excretion study of mosapride and its active des-p-fluorobenzyl and 4′-N-oxide metabolites in rats by ultra-high performance liquid chromatography-tandem mass spectrometry method. (1st February 2020) - Li, Kunjie; Jiang, Xu; Xiong, Zhili; Qin, Feng; Zhao, Longshan
Abstract: 1. Mosapride is a potent gastroprokinetic agent, and des-p-fluorobenzyl mosapride (M1) and mosapride-N-oxide (M2) are its two major active metabolites. 2. The validated ultra-high performance liquid chromatography-tandem mass spectrometry method was successfully applied to the distribution and excretion of mosapride and its two active metabolites. 3. Mosapride and its metabolites were distributed widely and rapidly in various tissues. The highest concentration of mosapride and M2 in both male and female rats was found in the duodenum, followed by cecum. 4. The excretion study showed that a total of 71.8% (37.6, 22.4 and 11.8% for urine, feces and bile, respectively) and 66.3% (35.7, 22.8 and 7.8% for urine, feces and bile) of administered dose was recovered from male and female excreta. M1 was excreted in the largest dose percentage, followed by mosapride and M2, and the total cumulative excretion amounts were about 36.9, 28.1 and 11.6% in male rat, while 24.3, 25.9 and 16.2% in female rat. The results demonstrated for the first time that M2 is one of the important excretion forms of mosapride, which is much higher than that of mosapride in urine. 5. This work could provide valuable information for further pharmacological and clinical studies of mosapride.